SUSTAINABLE FOREST MANAGEMENT IN INDONESIA’S FOREST LAW (POLICY AND INSTITUTIONAL FRAMEWORK) - Sri Wahyuni (Faculty of Law, Universitas Jenderal Soedirman, 2014)
Indonesia Forest Law No. 41 Year 1999 in article 46 states: “Forest protection and nature conservation aim at keeping the forest, forest area and its environment, so that protection, conservation functions and productions, is achieved in an optimal and sustainable”. With all issues that happen in Indonesia, so that Indonesia need to protect their forest and one of the way to do it is Sustainable Forest Management (SFM). SFM is the management of forest according to the principles of sustainable development. SFM uses very broad social, economic and environmental goals. All item of SFM are including also in the Indonesian Forest Law No. 41 year 1999. This paper would like to describe about Legal, Policy and Institutional framework to achieve the Sustainable Forest Management in Indonesia’s Forest Law, with normative research. Key words: forest, law, forest law, sustainable forest management